Use of Oxandrolone to Promote Growth in Neonates following Surgery for Complex Congenital Heart Disease: An Open‐Label Pilot Trial. (3rd June 2016) - Burch, Phillip T.; Spigarelli, Michael G.; Lambert, Linda M.; Loftus, Patrick D.; Sherwin, Catherine M.; Linakis, Matthew W.; Sheng, Xiaoming; LuAnn Minich, L.; Williams, Richard V.
Abstract: Objective: Malnutrition and poor weight gain, common in neonates following repair of complex congenital heart disease (CHD), are associated with increased morbidity and mortality. Oxandrolone, an anabolic steroid, improves weight gain in older children at high‐risk for growth failure. We sought to determine feasibility, safety, and efficacy of oxandrolone therapy in neonates following surgery for complex CHD. Design: Neonates with RACHS‐1 score >3 were eligible to receive open‐label oxandrolone for 28 days in this prospective pilot trial. There were 3 cohorts of 5 subjects receiving oxandrolone therapy under 3 specified dosage and preparation protocols: 0.1 mg/kg/day aqueous solution, 0.2 mg/kg/day aqueous solution, and 0.1 mg/kg/day preparation in medium chain triglyceride (MCT) oil. Age‐ and diagnosis‐matched neonates who underwent surgery, but received no oxandrolone, served as a control cohort. Anthropometric measurements, physical examination for virilization, safety labs, and adverse events were monitored. Results: Of 25 eligible patients, 15 consented (60%, 13/15 with Norwood procedure). There was no evidence of virilization, no changes in safety labs, and no serious adverse events related to oxandrolone among subjects receiving therapy. No subject met criteria for termination of study drug. There was a significant difference in change in weight‐for‐age z‐score among the four cohorts, with subjects receiving 0.1 mg/kg/day in MCT oil having the lowest decline during the study period (−1.8 ± 0.5 for controls, −1.7 ± 0.4 for 0.1 mg/kg/day aqueous, −1.0 ± 0.4 for 0.2 mg/kg/day aqueous, and −0.6 ± 0.7 for 0.1 mg/kg/day MCT oil, P = .012). Conclusions: Oxandrolone therapy at the doses studied appears safe in neonates after surgery for complex CHD. The decline in weight‐for‐age z‐score was lowest in those receiving the MCT oil preparation suggesting better bioavailability of this preparation and a potential growth benefit with oxandrolone therapy. Further investigation is needed to define optimal dosing and assess efficacy.